An update on autophagy disorders - Dafsari, Hormos Salimi; Martinelli, Diego; Saffari, Afshin; Ebrahimi-Fakhari, Darius; Fanto, Manolis; Dionisi-Vici, Carlo; Jungbluth, Heinz (Journal of inherited metabolic disease, 2025)
Macroautophagy is a highly conserved cellular pathway for the degradation and recycling of defective cargo including proteins, organelles, and macromolecular complexes. As autophagy is particularly relevant for cellular homeostasis in post-mitotic tissues, congenital disorders of autophagy, due to monogenic defects in key autophagy genes, share a common “clinical signature” including neurodevelopmental, neurodegenerative, and neuromuscular features, as well as variable abnormalities of the eyes, skin, heart, bones, immune cells, and other organ systems, depending on the expression pattern and the specific function of the defective proteins. Since the clinical and genetic resolution of EPG5-related Vici syndrome, the paradigmatic congenital disorder of autophagy, the widespread use of massively parallel sequencing has resulted in the identification of a growing number of autophagy-associated disease genes, encoding members of the core autophagy machinery as well as related proteins. Recently identified monogenic disorders linking selective autophagy, vesicular trafficking, and other pathways have further expanded the molecular and phenotypical spectrum of congenital disorders of autophagy as a clinical disease spectrum. Moreover, significant advances in basic research have enhanced the understanding of the underlying pathophysiology as a basis for therapy development. Here, we review (i) autophagy in the context of other intracellular trafficking pathways; (ii) the main congenital disorders of autophagy and their typical clinico-pathological signatures; and (iii) the recommended primary health surveillance in monogenic disorders of autophagy based on available evidence. We further discuss recently identified molecular mechanisms that inform the current understanding of autophagy in health and disease, as well as perspectives on future therapeutic approaches.
Online verfügbar: 17. Oktober 2024
Gesehen am 14.04.2025